MECHANISMS OF LABOR PRODUCTIVITY INCREASE WITHIN THE CONDITIONS OF MODERN SCIENTIFIC AND TECHNOLOGICAL DEVELOPMENT - A. O. Ivanov (Вестник университета)
Socio-economic development of Russia involves active scientific and technological development that stimulates economic growth. State priority is given to areas of scientific and technological development,  which stimulate innovative development of the domestic market and strengthen Russia’s position in the international arena. Scientific and technological development may face a number of administrative,  technological and institutional threats, levelling of which is possible through the creation of conditions, leading to an increase in labor productivity. The mechanisms of labor productivity increase, distributed according to the following factors of labor productivity growth, have been presented in the article, such as: material and technical, organizational and economic, socio-psychological, natural, socio-economic. The developed mechanisms of labor productivity increase take into account modern level of scientific and technological development and seem useful both in creating the policy of labor productivity increase in the framework of an individual enterprise, and in the development and implementation of state economic policy and national projects.